Anatomy-Zoology building - Unidentified artist (Colorado State University. Libraries, 1969)
Architectural drawing of CSU's new Anatomy building. CSU Collegian, October 29, 1969.
Not digitized by CSUL Digital Services.
Keywords: anatomy-zoology; anatomy; zoology